Observer-based single-phase robustness sliding mode controller for the pitch control of a variable speed wind turbine - Cong-Trang Nguyen; Chiem Trong Hien; Van-Duc Phan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
In this paper, a new observer-based single-phase robustness sliding mode controller (SPRSMC) is proposed for the pitch control of a variable speed wind turbine (VSWT) systems. The finding of this research includes two tasks: i) to ensure a global stability of the VSWT plant, the reaching phase in traditional sliding mode control (TSMC) technique is eliminated and ii) to guess the immeasurable variables of VSWT plants, a novel pitch angle output feedback controller is constructed based on the estimator tool and output information only. Firstly, a single-phase switching function is determined to eject the reaching phase in TSMC. Moreover, an immeasurable variable of the VSWT system is estimated by employing the suggested estimator tool. Next, a SPRSMC for VSWT plant is built based on the support of the estimator instrument and output data only. Furthermore, an appropriate requirement is founded by utilizing the linear matrix inequality (LMI) method for ensuring the robust stability of motion dynamics in sliding mode. Finally, the solution of the suggested control is confirmed the three-blade wind turbine with a 5-MW utilizing the wind turbine simulator fatigue, aerodynamics, structures, and turbulence (FAST) code and the National Renewable Energy Laboratory (NREL).